Ginsenoside Rb1 Enhances Atherosclerotic Plaque Stability by Improving Autophagy and Lipid Metabolism in Macrophage Foam Cells - Qiao, Lei; Zhang, Xue; Liu, Minghao; Liu, Xiaoling; Dong, Mei; Cheng, Jing; Zhang, Xinyu; Zhai, Chungang; Song, Yu; Lu, Huixia; Chen, Wenqiang (Frontiers in Pharmacology, 2017)
Atherosclerosis (AS) is a lipid-driven disease in which macrophage foam cells play a critical role by increasing vascular lipid accumulation and contributing to plaque instability. Ginsenoside Rb1 (Rb1), the most abundant active component of ginseng, has been found potently to promote lipid metabolism and attenuate lipid accumulation. However, the underlying mechanisms remain unclear. In this study, the effects of Rb1 on lipid accumulation and plaque stability were investigated both in vitro and in vivo by using primary peritoneal macrophages isolated from C57BL/6 mice and an AS model in ApoE-/- mice. The results showed that Rb1 reduced lipid accumulation both in macrophage foam cells and atherosclerotic plaques. Rb1 treatment promoted plaque stability by modifying plaque composition via the activation of autophagy both in vitro and in vivo. Transmission electron microscopy further showed an increased accumulation of autophagolysosomes in Rb1-treated macrophage foam cells. However, the modulation of lipid accumulation by Rb1 was attenuated by autophagy blockage using autophagy-related gene 5 (Atg5) small interfering RNA (siRNA) in vitro. In addition, Rb1 notably increased AMPK phosphorylation both in vitro and in vivo, and the AMPK inhibitor compound C abolished the Rb1-induced autophagy in macrophage foam cells. In conclusion, ginsenoside Rb1 reduced lipid accumulation in macrophage foam cells and enhanced atherosclerotic plaque stability by the induction of macrophage autophagy. Our study provides new evidence for the possible use of Rb1 in the prevention and treatment of AS.